Latin America's Middle Sectors Key Players in a Renewed Social Contract? - Pietikäinen, Anna (OECD Publishing, 2010)
A strengthened social contract in Latin American countries relies on the improved quality of public services such as health and education, which would build a constituency for a broader tax base. Latin American middle-income sectors express strong support for democracy but they are critical of how it works, largely due to the low quality of public services. Fiscal policy is at the heart of the state's relationship with its citizens - all the more so in Latin America, given the weak social contracts and the consolidation of its democracies
Keywords: Development